Towards a Christian Philosophy - Owens, Joseph, 1908-2005 (Studies in philosophy and the history of philosophy ;, 2019)
Brings together a lifetime of work on the problems presented by the notion of a Christian philosophy, debates whether a Christian philosophy is possible, and outlines the steps for its development.